FLASH radiotherapy at a crossroads: a bibliometric perspective on progress and challenges - Peng Wang; Yugeng Gao; Can Chen; Xiaoxin Zhao; Yuying Zhang; Taorui Liu; Haoran Jiang; Zhe Wang; Xiang Zhao; Jianjun Li (Discover Oncology)
Abstract Background Flash radiotherapy (FLASH-RT), an emerging modality utilizing ultra-high dose-rate (UHDR) irradiation (typically > 40 Gy/s), has demonstrated a unique capacity to preserve normal tissue integrity while maintaining tumor control efficacy compared to conventional radiotherapy. Despite exponential growth in FLASH-RT research over the past decade, its scientific landscape has not yet been systematically characterized through bibliometric analysis. This study only includes articles from the Web of Science Core Collection (WoSCC) and is limited to English-language publications, which may introduce database and language biases. Methods Relevant articles and reviews on FLASH-RT were retrieved from the WoSCC database. Bibliometric analysis and scientific knowledge mapping were performed using the R packages Bibliometrix, CiteSpace, and VOSviewer, in conjunction with the online analytical tools provided by Web of Science (WoS). Results A total of 572 publications from 2013 to 2025, spanning 179 countries/regions and involving 2,049 institutions, were analyzed. The United States, Switzerland, and China were the leading contributors. The University of Lausanne had the highest research output. These publications appeared in 96 different journals, with Medical Physics contributing the most studies. Among 2995 authors, Vozenin MC had the highest publication count and H-index, while Favaudon V’s papers received the most citations. Frequent keywords included irradiation, flash radiotherapy, radiation therapy, and cells. Keyword clustering revealed eleven major research directions, primarily focusing on pencil beam scanning and dosimetry. Conclusion This first bibliometric analysis of FLASH-RT research highlights key trends, influential contributors, and challenges. These findings provide valuable insights into research frontiers and hotspots, guiding future studies and collaborations.